Development of an operator interface for a multi-sensor overhead surveillance system - Mayo, A.; Bocknek, D.; Blake, C.; Boswell, Brian; Rittenhouse, R.; Beling, P.; Wang, J. (2011)
In this project, we designed an efficient way to manage automated surveillance system data and present it to an operator. We created an operator interface and a message-exchange based data management system to store and communicate surveillance information between a ground-based operator and a simulated surveillance network with limited observational resources. Our system comprises a communication management system, historical database, web application, and browser-based operator interface. We created a near real-time, message-exchange based communication method by using a database as a message processing buffer. Our system processes relevant surveillance data and presents it to the operator in a manageable view within a flexible, scalable, browser-based interface that allows the operator to influence the surveillance system's resource allocation to reflect changing situational priorities. Our interface balances simplicity for the operator with sufficient operational capability. Additionally, our design is general in that may be used with multiple surveillance systems and simulations without requiring any modifications to our system. This generality affords our system the ability to test multiple potential surveillance systems. By implementing this design, we have provided a flexible, non-traditional solution that aids the management and integration of an otherwise fragmented surveillance system. © 2011 IEEE.